Intercultural Interpretation: The Study of the Qur'an in Translation of the Islamic University of Indonesia 2020 Edition - Nawawi, Imam (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study examines the translation of the Quran by H. Zaini Dahlan edited by KH. Ahmad Bahauddin Noersalim, published by UII Press Yogyakarta 2020. This qualitative type of research uses a literature research design with a multidisciplinary approach; translation theory, language logic, language structure, and socio-linguistic space. This study found six (6) main points: first, the problematic problem of translating the UII version of the Quran, second, meaningful translation, third, the use of language logic, fourth, the influence of Arabic syntax, fifth, the creation of pace, character and reader hierarchy, and sixth, originality and local cultural wisdom.